FLIPPED CLASSROOM BERBANTUAN VIDEO AI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI MOTIVASI BELAJAR - Kansha Aurel Honey Kayla; Wakhid Fitri Albar (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study is motivated by the low level of students’ mathematical problem-solving ability and the need for contextual and adaptive learning innovations through the use of technology. This study aims to determine the improvement of students’ mathematical problem-solving ability through the implementation of a flipped classroom model assisted by artificial intelligence (AI)-based video with an ethnomathematics approach, as well as to examine the role of learning motivation. This research employed a mixed methods approach with a sequential explanatory design. The quantitative phase used a one group pretest-posttest design involving 31 students of class VIII D at SMP Negeri 1 Randudongkal, while the qualitative phase was conducted through interviews and observations involving 9 students as interview subjects. Quantitative data were analyzed using descriptive statistics, normality test, one sample t-test, proportion test, paired sample t-test, N-gain, and simple linear regression, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The results showed an improvement in students’ mathematical problem-solving ability, indicated by an increase in the average score from 68.83 to 83.83, with classical completeness reaching 100%. However, learning motivation did not have a significant effect on mathematical problem-solving ability, with a contribution of 1.4%. Qualitative findings revealed that learning motivation plays a role in enhancing students’ engagement in the learning process. Therefore, the implementation of a flipped classroom model assisted by AI-based video with an ethnomathematics approach is effective in improving mathematical problem-solving ability and creating more contextual and adaptive learning. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan pemecahan masalah matematis peserta didik serta perlunya inovasi pembelajaran yang kontekstual dan adaptif melalui pemanfaatan teknologi. Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan pemecahan masalah matematis peserta didik melalui penerapan model flipped classroom berbantuan video berbasis artificial intelligence (AI) bernuansa etnomatematika serta mengkaji peran motivasi belajar. Penelitian menggunakan pendekatan mix methods dengan desain sequential explanatory. Tahap kuantitatif menggunakan desain one group pretest-posttest yang melibatkan 31 peserta didik kelas VIII D di SMP Negeri 1 Randudongkal, sedangkan tahap kualitatif dilakukan melalui wawancara dan observasi dengan melibatkan 9 peserta didik sebagai subjek wawancara. Analisis data kuantitatif meliputi statistik deskriptif, uji normalitas, uji one sample t-test, uji proporsi, uji paired sample t-test, perhitungan N-gain, dan regresi linear sederhana, sedangkan analisis kualitatif dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan adanya peningkatan kemampuan pemecahan masalah matematis yang ditunjukkan oleh kenaikan rata-rata dari 68,83 menjadi 83,83 dengan ketuntasan klasikal mencapai 100%. Namun, motivasi belajar tidak berpengaruh signifikan terhadap kemampuan pemecahan masalah matematis dengan kontribusi sebesar 1,4%. Temuan kualitatif menunjukkan bahwa motivasi belajar tetap berperan dalam meningkatkan keterlibatan peserta didik dalam proses pembelajaran. Dengan demikian, penerapan model flipped classroom berbantuan video AI bernuansa etnomatematika efektif dalam meningkatkan kemampuan pemecahan masalah matematis dan menciptakan pembelajaran yang lebih kontekstual serta adaptif.